1997
DOI: 10.1074/jbc.272.22.14001
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Modification of Nuclear Proteins by a Novel Ubiquitin-like Molecule

Abstract: Sentrin is a novel ubiquitin-like protein that protects cells against both anti-Fas and tumor necrosis factorinduced cell death. Antiserum recognizing the N terminus of sentrin revealed the presence of a 18-kDa sentrin monomer, a 90-kDa band (p90), and multiple high molecular mass bands. Because sentrin possesses the conserved Gly-Gly residues near the C terminus, it is likely that these additional bands represent conjugation of sentrin to other proteins in a manner that is similar to the ubiquitination pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
167
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 162 publications
(171 citation statements)
references
References 22 publications
4
167
0
Order By: Relevance
“…In fact, free SUMO-1 protein can be detected in Saos-2 cells (Figure 7a) making it questionable whether one could modulate the levels of sumoylation by co-transfection with a SUMO-1-expressing plasmid. To overcome this obstacle, we used a SUMO-1 construct (SUMO-4aa) with a deletion of the last four amino acids in a transactivation assay: it was shown that cleavage of the last four amino acids was required for the activation of SUMO-1 protein (Mahajan et al, 1997;Kamitani et al, 1997). As a negative control, we used another SUMO-1 construct (SUMO-6aa) with deletion of the last six amino acids, which was shown previously to be defective in sumoylation .…”
Section: Resultsmentioning
confidence: 99%
“…In fact, free SUMO-1 protein can be detected in Saos-2 cells (Figure 7a) making it questionable whether one could modulate the levels of sumoylation by co-transfection with a SUMO-1-expressing plasmid. To overcome this obstacle, we used a SUMO-1 construct (SUMO-4aa) with a deletion of the last four amino acids in a transactivation assay: it was shown that cleavage of the last four amino acids was required for the activation of SUMO-1 protein (Mahajan et al, 1997;Kamitani et al, 1997). As a negative control, we used another SUMO-1 construct (SUMO-6aa) with deletion of the last six amino acids, which was shown previously to be defective in sumoylation .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, one model, which remains to be tested, is that complexes containing Cul2 and elongins B and C target certain proteins for ubiquitin-dependent proteolysis. A more speculative model, given that elongin B contains a ubiquitin-like domain, is that elongin B itself becomes covalently linked to certain proteins, such as has been observed for the ubiquitinlike protein named either GMP1, SUMO-1, or Sentrin (20,33). In either case, pVHL competes with elongin A in vitro for binding to elongins B and C (6).…”
Section: Discussionmentioning
confidence: 99%
“…The notion that SUMO-1 may be involved in targeting proteins to the nuclear pore complex came from studies of SUMO-1 conjugated RanGAP1 which is known to bind to the nuclear pore complex (24,37,39,40). SUMO-1 conjugates also have been shown to be primarily located in the nucleus (54) and often targeted to the nuclear bodies as most evidently demonstrated in the case of PML (52). One could speculate that SUMO-1 conjugated hTOP1 molecules in cells treated with CPT are either targeted to the nuclear pore complex for nuclear export or to the nuclear bodies.…”
Section: Discussionmentioning
confidence: 99%